Pendidikan Antropologi dan Pembangunan Indonesia - Amri Marzali (Antropologi Indonesia, 2000)
This article was written in response to a challenge put forth by two non-anthropologists over the role of anthropologists in Indonesian national development. The challenge was made by the late Dr. Y.B. Mangunwijaya (Kompas 24 January 1996) and Dr. Benjamin Lumenta (Kompas 29 January 1996). In fact, a response was given by Prof. Parsudi Suparlan (Kompas3 February 1996) and the author (Republika 2 May 1996). Also related to the matter is an article by Prof. S. Budhisantoso (Republika 24 May 1996).This article is an extension of the author's own article that appeared in Republika of May2, 1996. He finds that his ideas on the role of anthropologists in national development could not be covered adequately in the brief newspaper article, and requires an extended and serious discussion-even more so since the present articles touches upon the anthropological education system in Indonesia, specifically at the Department of Anthropology at the University of Indonesia. Thus, the article brings forth three main points, that is the role of anthropologists in Indonesia, the development of the anthropological education system in Indonesia, and Indonesian development.